Comprensión lectora en el aprendizaje de estudiantes de cuarto grado de la Unidad Educativa Santiago Fernández García, periodo 2023-2024 - Sarango Moreno, Kely Estefania (2024)
Reading comprehension is a skill of essential importance in education, since it constitutes the main source of knowledge in all subjects. It is vital to stimulate reading from an early age in children, and continue to cultivate it throughout life, because this will contribute significantly to both personal and academic success. This paper’s general objective was to analyse fourth grade students’ reading comprehension in the learning environment. We selected a population of the teacher and fourth grade students, resulting in a total of 1 teacher and 27 students. This research was of a qualitative approach, descriptive type, non-experimental design and cross-sectional; For its development we used the scientific deductive and analytical methods; The interview and observation techniques were used to obtain information regarding the two study variables. The results evidenced that students have not yet reached a level of critical comprehension, because in some cases children are still at a phonic reading stage, and there are certain confusions in the recognition of letters, thus leading to the conclusion that the inefficient reading comprehension in students may hinder their comprehension of complex texts and the academic performance in various subjects in the future. Finally, it is concluded that fourth grade students show a remarkable interest in reading, and have a reading comprehension that is appropriate for their level, considering that there are different levels of comprehension. However, some students still face problems such as getting confuse when recognizing letters and finding it difficult to pronounce some words correctly, which could significantly affect their academic performance.